Cu-catalyzed arylation of the amino group in the indazole ring: regioselective synthesis of pyrazolo-carbazoles. Issue 5 (4th December 2014) - Anil Kumar, K.; Kannaboina, Prakash; Dhaked, Devendra K.; Vishwakarma, Ram A.; Bharatam, Prasad V.; Das, Parthasarathi
Abstract : Arylated aminoindazoles were synthesized by copper-catalyzed C–N bond cross-coupling with boronic acids. These were then transformed to pyrazolo-carbazoles by Pd-catalyzed regioselective cross-dehydrogenative coupling. Abstract : Cu(ii )-catalyzed cross-coupling of various aryl boronic acids with 5 and 6-amino indazoles has resulted in (arylamino)-indazoles. These (arylamino)-indazoles have been utilized in synthesizing medicinally important pyrazole-fused carbazoles via Pd(ii )-catalyzed cross-dehydrogenative coupling (CDC). This combined N-arylation/C–H arylation strategy has been successfully applied to the regioselective synthesis of polyheterocycles 3, 6-dihydropyrazolo[3, 4- c ]carbazoles and 1, 6-dihydro pyrazolo[4, 3- c ]carbazoles. Quantum chemical analysis has been carried out to understand the regioselectivity and to trace the potential energy surface of the entire reaction upon 5- N -aryl-indazole conversion to the corresponding carbazole.